2011
DOI: 10.1149/2.045201jes
|View full text |Cite
|
Sign up to set email alerts
|

Study of Solid Electrolyte Interface Formation and Lithium Intercalation in Li-Ion Batteries by Acoustic Emission

Abstract: This paper has the aim to demonstrate that Acoustic Emission (AE) is an appropriate technique to become a diagnostic tool for state of charge, state of health and state of security of lithium-ion cells. These issues are actually key parameters for both performance and durability improvement. The presented results deal with the monitoring of the SEI formation and the first lithium ion intercalation on the surface and inside the graphite electrode. AE events coming from different sources have thus been identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 20 publications
(19 reference statements)
2
37
0
Order By: Relevance
“…Accordingly, the imaging data in combination with the EIS results support our conclusion that the first increase in acoustic activity is because of cSEI formation (see also Figure S8 of the Supporting Information for high-and low-magnification SEM images recorded after charging to different voltages in the initial cycle). [39][40][41] This also corroborates indirectly our assumption that the AE detected beyond the monoclinic phase and up to the upper cutoff voltage is due to crack formation (Figure 4c and d), and this is further confirmed by direct comparison with the following cycles. In the second charge cycle, the already formed cSEI was clearly visible by SEM until~3.8 V. Only for higher voltages (� 4.0 V), notable fracture of the primary and Batteries & Supercaps secondary particles was apparent (see Figure S9 of the Supporting Information).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Accordingly, the imaging data in combination with the EIS results support our conclusion that the first increase in acoustic activity is because of cSEI formation (see also Figure S8 of the Supporting Information for high-and low-magnification SEM images recorded after charging to different voltages in the initial cycle). [39][40][41] This also corroborates indirectly our assumption that the AE detected beyond the monoclinic phase and up to the upper cutoff voltage is due to crack formation (Figure 4c and d), and this is further confirmed by direct comparison with the following cycles. In the second charge cycle, the already formed cSEI was clearly visible by SEM until~3.8 V. Only for higher voltages (� 4.0 V), notable fracture of the primary and Batteries & Supercaps secondary particles was apparent (see Figure S9 of the Supporting Information).…”
Section: Resultssupporting
confidence: 88%
“…[17,18] Based on both test measurements and literature data, a possible contribution of the lithium anode to the acoustic activity can be neglected (see Figure S2 of the Supporting Information). [39,49] Using electrochemical impedance spectroscopy (EIS), Zhan et al suggested the successive formation/growth of cSEI layers with different properties: a resistive layer followed by its conversion into a more conductive cSEI. [50,51] Hence, the further increase in acoustic activity from 3.9 to 4.3 V (HV region) may be explained by growth/conversion of the initial cSEI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kircheva et al revealed that the acoustic hits or the absolute energy released recorded in the first cycle far outnumbered those in the subsequent cycles ( Figure 58b). 644 They attributed the source of these acoustic events to the formation of SEI accompanied by the generation of gaseous products as well as fracture of graphite crystallites during Li + -intercalation. Note that the largest accumulated energy occurred during the voltage range 1.5−0.75 V, which was considered to be the potential range where carbonate molecules start to decompose reductively.…”
Section: Electronmentioning
confidence: 99%
“…Rhodes et al [21] monitored particle fracture in Sibased anodes of Li-ion batteries and showed that the fracture of Si particles can be modelled using a thermal analogy model [22]. This technique has also been applied to Li/NiSb2 batteries [23], solid electrolyte interface (SEI) formation and Li intercalation in Li-ion batteries [24], solid oxide fuel cell seal cracking [25,26], Nafion dehydration [27], and flooding [28] and localised operation [29] in polymer electrolyte membrane fuel cells.…”
Section: Introductionmentioning
confidence: 99%